Burden and Prevention of HPV. Knowledge, Practices and Attitude Assessment Among Pre-Adolescents and their Parents in Italy - Icardi, Giancarlo; Costantino, Claudio; Guido, Marcello; Zizza, Antonella; Restivo, Vincenzo; Amicizia, Daniela; Tassinari, Federico; Piazza, Maria F.; Paganino, Chiara; Casuccio, Alessandra; Vitale, Francesco; Ansaldi, Filippo; et al. (Current Pharmaceutical Design, 2020)
Despite infections due to HPV nowadays represent the most common sexually transmitted diseases worldwide with recognized effective and safe preventive strategies, knowledge, attitudes; however, awareness on HPV is considerably low. The present study has two main objectives: 1. To conduct a literature review to analyze the evolution of preventive tools, the complexity of the vaccine choice process, and the challenges posed by HPV vaccine hesitancy and refusal among pre-adolescents and their parents; 2. To assess knowledge, practices and attitudes toward HPV infection and vaccination in a sample of Italian pre-adolescents and their parents. The observational study was carried out through the use of two anonymous and self-administered pre- and postintervention questionnaires dedicated to the target populations. Between the administrations of the pre- and postintervention questionnaires, an educational intervention on HPV infection and related diseases, and prevention strategies was conducted. All participants demonstrated suboptimal knowledge and positive attitudes in the preintervention questionnaire. Higher levels of knowledge and attitudes were observed among pre-adolescents thatused social networks and had heard of sexually transmitted diseases at home/school/physician and from parents and also who had heard of HPV from General Practitioners, Gynecologists, family members and newspapers. A significant increase in HPV vaccination awareness was observed among pre-adolescents after the educational sessions. Health education programs aimed at increasing knowledge, attitudes and awareness on HPV are needed to implement the outcomes of HPV immunization programs, especially if supported by the physicians involved in counselling and recommendation processes.
Keywords: adolescents